The power of deliberation international law, politics, and organizations - Johnstone, Ian, 1960- (New York ; Oxford : Oxford University Press, 2011)
Arguing about matters of public policy is ubiquitous in democracies. The ability to resolve conflicts through peaceful contestation is a measure of any well-ordered society. This book challenges the assumption that arguing is mere lip service with no real impact on the behavior of states or the structure of the international system.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: International law; International relations; Discourse analysis